Motor imagery in children with DCD: A systematic and meta-analytic review of hand-rotation task performance. (April 2019) - Barhoun, Pamela; Fuelscher, Ian; Kothe, Emily Jane; He, Jason L.; Youssef, George J.; Enticott, Peter G.; Williams, Jacqueline; Hyde, Christian
Highlights: This is the first review summarizing HRT performance in children with DCD. Children with DCD engage in MI during HRT performance similarly to controls. However, they show consistent HRT performance deficits irrespective of outcome metric. Group difference effect sizes vary considerably depending on outcome measure. The efficiency metric offers the most sensitive measure for detecting group differences. Abstract: This is the first review to quantitatively summarise evidence evaluating MI functioning in children with DCD compared to controls based on the hand rotation task (HRT). Specifically, MI performance was assessed using three different behavioural performance measures on the HRT (i.e., reaction time, accuracy and efficiency). Eight studies were included for quantitative analysis, yielding data for 176 and 198 children with and without DCD respectively. While children with DCD consistently used MI across all measures of the task, they continually demonstrated reductions in HRT performance relative to controls. Additionally, group differences appeared to be strongest and more commonly detected when using the IES (mean inverse efficiency-IES) metric on the HRT. These effects did not differ statistically as a function of instruction type. In support of the internal modelling deficit hypothesis, group effects suggested children with DCD demonstrate broad reductions in HRT performance relative to controls. However, consideration of effect size and study level analysis showed the ability for an individual study to detect these effects differs considerably depending on the outcome metric adopted.